Negotiating Poetic and Musical Structure: The Adaptation of Pupuh Sinom in Tembang Sunda Cianjuran - Sudrajat, Mustika Iman Zakaria; Alamsyah, Yosep Nurdjaman (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2026)
In the context of Sundanese culture, pupuh is a literary form that has static rules. As a literary form, pupuh is often used as a guide for composing song lyrics in Sundanese traditional vocal art, thereby leading to interactions with musical elements. In this case, this interaction happens to the pupuh Sinom, as mentioned in the lyrics of the tembang Sunda cianjuran song entitled Sinom Degung and Gawil Tarik. In this context, a negotiation occurs between the conventions of the pupuh Sinom and the song's melody, ultimately leading to the pupuh Sinom's adaptation. Using a descriptive analysis approach, this study aims to understand the event through the conventions of pupuh Sinom and the melody of the tembang Sunda cianjuran song. This analysis shows that the conventions of pupuh, specifically padalisan number and guru lagu, can preserve their static nature. In contrast, the guru wilangan number becomes dynamic due to the insertion of suffixes and word repetition, which allows for greater flexibility and variation in the performance of the tembang Sunda cianjuran songs. Finally, this study reconceptualizes the understanding of pupuh from a static framework into a dynamic framework. Furthermore, these results help shape the world of ethnomusicology, especially those related to the dynamic relationship between poetry and music.